Packing a Pair of Ellipses

Geometry Level 5

Two non-overlapping and equal ellipses of eccentricity e e are to be packed in a unit square such that they occupy the maximum possible area. The given animation shows the optimal packing for different values of e e as e e varies between 0 0 and 1 1 .

There is a critical number e 0 e_0 such that for 0 < e e 0 {0<e\leq e_0} , the optimal packing occurs when the ellipses are symmetric about the diagonals of the square. However, for e 0 < e < 1 {e_0<e<1} , the optimal packing is not symmetric about the diagonals. Find the distance between the centers of the two ellipses corresponding to the case e = e 0 e=e_0 .

The answer is l m l n \dfrac{l\sqrt{m}-\sqrt{l}}{n} for coprime integers l , m , n {l,m,n} . Submit l + m + n {l+m+n} .


Hint: Study the following paper: Optimal packings of two ellipses in a square


The answer is 19.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

In Optimal packings of two ellipses in a square , Thierry Gensane and Pascal Honvault prove that the critical number e 0 {{e}_{0}} occurs when the aspect ratio of the ellipse is

b a = E 0 = 6 3 3 11 0.8198 ( 1 ) \dfrac{b}{a}={{E}_{0}}=\sqrt{\dfrac{6\sqrt{3}-3}{11}}\approx 0.8198 \ \ \ \ \ (1) where a a and b b are the semi-major axis and the semi-minor axis of the ellipse.

As seen in the figure, point A A lies on the director circle of one of the two ellipses, i.e. on a circle that has the same center O 1 {{O}_{1}} as the ellipse and with radius r = a 2 + b 2 ( 2 ) r=\sqrt{{{a}^{2}}+{{b}^{2}}} \ \ \ \ \ (2)

Combining relations ( 1 ) (1) and ( 2 ) (2) we get r = ( b E 0 ) 2 + b 2 = b 1 + E 0 2 E 0 r=\sqrt{{{\left( \dfrac{b}{{{E}_{0}}} \right)}^{2}}+{{b}^{2}}}=b\dfrac{\sqrt{1+{{E}_{0}}^{2}}}{{{E}_{0}}} Furthermore,

[ A B D ] = 1 2 A K B D = 1 2 A B A D A K B D = A B 2 ( r + b ) 2 = 1 ( b 1 + E 0 2 E 0 + b ) 2 = 1 2 b ( 1 + E 0 2 E 0 + 1 ) = 2 2 b = 2 E 0 1 + E 0 2 + E 0 \begin{aligned} \left[ ABD \right]=\dfrac{1}{2}AK\cdot BD=\dfrac{1}{2}AB\cdot AD & \Rightarrow AK\cdot BD=A{{B}^{2}} \\ & \Rightarrow \left( r+b \right)\sqrt{2}=1 \\ & \Rightarrow \left( b\dfrac{\sqrt{1+{{E}_{0}}^{2}}}{{{E}_{0}}}+b \right)\sqrt{2}=1 \\ & \Rightarrow 2b\left( \dfrac{\sqrt{1+{{E}_{0}}^{2}}}{{{E}_{0}}}+1 \right)=\sqrt{2} \\ & \Rightarrow 2b=\dfrac{\sqrt{2}{{E}_{0}}}{\sqrt{1+{{E}_{0}}^{2}}+{{E}_{0}}} \\ \end{aligned} Plugging the value of E 0 {{E}_{0}} , we find that the distance between the centers of the two ellipses is O 1 O 2 = 2 b = 6 2 6 11 \left| \overline{{{O}_{1}}{{O}_{2}}} \right|=2b=\frac{6\sqrt{2}-\sqrt{6}}{11} For the answer, l = 6 l=6 , m = 2 m=2 , n = 11 n=11 , thus, l + m + n = 19 l+m+n=\boxed{19} .

David Vreken
Feb 21, 2021

Place the unit square so that its vertices are at ( ± 2 2 , ± 2 2 ) (\pm \frac{\sqrt{2}}{2}, \pm \frac{\sqrt{2}}{2}) , so that the edges are represented by the lines y = ± x ± 2 2 y = \pm x \pm \frac{\sqrt{2}}{2} , and let the ellipses have semi-major axes of a a and a semi-major axes of b b with centers at ( ± b , 0 ) (\pm b, 0) so that they are represented by the equations ( x ± b ) 2 b 2 + y 2 a 2 = 1 \cfrac{(x \pm b)^2}{b^2} + \cfrac{y^2}{a^2} = 1 .

According to the paper in the given hint, the aspect ratio E 0 E_0 of each ellipse is E 0 = 6 3 3 11 = a b E_0 = \sqrt{\cfrac{6\sqrt{3} - 3}{11}} = \cfrac{a}{b} , so a 2 = ( 6 3 3 ) b 2 11 a^2 = \cfrac{(6\sqrt{3} - 3)b^2}{11} , and substituting this into the equation of the ellipse on the right and rearranging gives 11 ( x b ) 2 + ( 6 3 3 ) y 2 = 11 b 2 11(x - b)^2 + (6\sqrt{3} - 3)y^2 = 11b^2 .

To be tangent to the line y = x + 2 2 y = -x + \frac{\sqrt{2}}{2} , the ellipse 11 ( x b ) 2 + ( 6 3 3 ) y 2 = 11 b 2 11(x - b)^2 + (6\sqrt{3} - 3)y^2 = 11b^2 will intersect it at only one x-value, so the discriminant of 11 ( x b ) 2 + ( 6 3 3 ) ( x + 2 2 ) 2 = 11 b 2 11(x - b)^2 + (6\sqrt{3} - 3)(-x + \frac{\sqrt{2}}{2})^2 = 11b^2 will be 0 0 . In other words, 22 b 2 + 12 6 b 6 2 b 6 3 + 3 = 0 22 b^2 + 12 \sqrt{6} b - 6 \sqrt{2} b - 6 \sqrt{3} + 3 = 0 , which solves to b = 6 2 6 22 b = \cfrac{6\sqrt{2} - \sqrt{6}}{22} .

The distances between the centers of the two ellipses is then 2 b = 6 2 6 11 2b = \cfrac{6\sqrt{2} - \sqrt{6}}{11} , so l = 6 l = 6 , m = 2 m = 2 , n = 11 n = 11 , and l + m + n = 19 l + m + n = \boxed{19} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...